The Minimal Translation Machinery: What We Can Learn From Naturally and Experimentally Reduced Genomes - Garzón, María José; Reyes-Prieto, Mariana; Gil, Rosario (Frontiers in Microbiology, 2022)
The current theoretical proposals of minimal genomes have not attempted to outline the essential machinery for proper translation in cells. Here, we present a proposal of a minimal translation machinery based on (1) a comparative analysis of bacterial genomes of insects’ endosymbionts using a machine learning classification algorithm, (2) the empiric genomic information obtained from Mycoplasma mycoides JCVI-syn3.0 the first minimal bacterial genome obtained by design and synthesis, and (3) a detailed functional analysis of the candidate genes based on essentiality according to the DEG database (Escherichia coli and Bacillus subtilis) and the literature. This proposed minimal translational machinery is composed by 142 genes which must be present in any synthetic prokaryotic cell designed for biotechnological purposes, 76.8% of which are shared with JCVI-syn3.0. Eight additional genes were manually included in the proposal for a proper and efficient translation.